TEACHING PROFESSION AND ITS INTERPRETATION IN THE NOVEL “BETWEEN TWO DOORS” - Soberova, Mohira (FILOLOGIYA UFQLARI JURNALI, 2024)
Abstract: This article will talk about the importance of the teaching profession in spiritual and moral education in a person’s life. The social injustice that reigned in the past through the teacher Samad in the novel by O’tkir Hoshimov “Between two doors” is described by the fact that the attitude of some officials of that time to teachers is sometimes described in its own way, and sometimes on the basis of events that shook the heart of the hero’s language.